PENEGAKAN HUKUM DISIPLIN ANGGOTA POLISI REPUBLIK INDONESIA DALAM PERSPEKTIF GOOD GOVERNANCE & CLEAN GOVERNMENT - Gusti Ayu Kade Komalasari; Ni Ketut Wiratni; Anak Agung Gde Putra Arjawa (Universitas Mahendradatta, 2021)
The Republic of Indonesia National Police (Polri) as one of the institutions that carry out the public service function is required to be able to provide the best service to the community by displaying professional and reliable unity performance in their fields. The Criminal Procedure Code, gives a role to the National Police of the Republic of Indonesia to carry out the tasks of investigation and investigation of criminal acts (generally) without limitation of the power of the nature as long as it is included in the scope of public law. Based on the descriptions in the background, the problem above, the problems that can be formulated in this study are: How is the Law Enforcement of Polri's Discipline in Realizing Good Governance and Clean Governance, What obstacles are faced by Polri's Discipline Enforcement in realizing Good Governance and clean governance The theory used to analyze the problems of the Law State Theory, Hirarkhi Theory Legal Norms, Authority Theory, Law Enforcement Theorem, Government Concepts and Clean Government This type of research is normative legal research supported by empirical legal research. The approach used by the author is the Law approach (Statute approach), legal concept analysis approach (analytical conseptual approach), comparative approach. Sources of Primary Legal Materials and secondary legal materials, namely materials that provide an explanation of primary legal materials, such as the results of seminars or other scientific meetings, Secondary legal material is the Legal Material Collection Technique carried out by a card system (collecting system) material both legislation, documents, library materials and other research results related to the subject matter. Processing techniques and legal material analysis, carried out qualitatively, legal materials are collected and analyzed descriptively (in parallel and coherently) in the form of description. Conceptual law enforcement and law enforcement as a process is realized with an indicator that the factors that influence the implementation of disciplinary law enforcement by Polri are guided by: Law enforcement / personal rules, infrastructure facilities that need to be held for disciplinary law enforcement processes for police members in cultural factors, Constraints - constraints faced by Polri Discipline Enforcement in realizing Good Governance and Clean Governance. The police are expected to behave and behave in a consistent manner with the vision, mission, code of ethics built by the Indonesian National Police. In its implementation there is still the interference of state officials, the political elite towards the implementation of Polri's duties so as to influence the disciplinary members of the National Police.